EuroKarst 2016, Neuchâtel : advances in the hydrogeology of karst and carbonate reservoirs - Renard, Philippe, 1967-; Bertrand, Catherine (Springer, 2017)
This book presents the latest advances in the field of karst hydrogeology and carbonate reservoirs. These include, but are not limited to: geomorphology of karst, flow and solute transport in karst; innovative metrology; modelling; speleogenesis and geology of carbonate reservoirs; deep reservoir exploration and production; water management and protection in karst environments; contaminant migration and chemical behavior; hydrochemistry and regional aquifer studies. EuroKarst offers a platform for professional exchanges between field practitioners and academic researchers. It is the European biennial conference on the hydrogeology of karst and carbonate reservoirs. It is organized every two years by the Universities of Neuchâtel (Switzerland), Besançon (France), and Malaga (Spain).
Abstract.
Keywords: Karst -- Congresses.; Carbonate reservoirs -- Congresses.; Hydrogeology -- Congresses.; elektronické knihy; electronic books